IMPLEMENTASI PERATURAN BUPATI BADUNG NO. 24 TAHUN 2017 TENTANG PENGURANGAN PAJAK BUMI DAN BANGUNAN DALAM UPAYA MENGURANGI ALIH FUNGSI LAHAN PERTANIAN DI KECAMATAN MENGWI, KABUPATEN BADUNG - Kurniadewi, Annisa Rosdiana; Yasintha, Putu Nomy; Anik Prabawati, Ni Putu (CITIZEN CHARTER, 2020)
ABSTRACTÂ The Regent Regulation No. 24 of 2017 concerning the deduction of land and building tax regulates deduction of the tax on house and agricultural land under certain conditions. This policy has a purpose for prospering the community and protecting the agricultural land in Badung Regency. This study aimed to find out the application of the policies on agricultural land in Mengwi District, Badung regency in order to decrease the agricultural land conversion based on the policy implementation theory by Van Meter and Van Horn. The result of the analysis shows that implementation of the policy has achieved good result on some indicators, such as: resources, relationship between organizations, social, economy, politics conditions, and implementer disposition. However, itâ€™s not achieve the maximum result on standard and target indicators and the characteristics of implementing agent because the objectives of the policy have not been achieved and the lack of field supervision. Keywords: Implementation, Conversion of Agricultural Land, Land and Building Tax.